Types of Speaking Anxiety Experienced by EFL Students During Classroom Presentations: A Case Study at IAIN Bone - Andi Winda Faradiba; Syarifuddin Dollah; Fitriyani Bakri (International Journal of Language, Education, and Literature, 2026)
This study explores the experiences of English as a Foreign Language (EFL) students in dealing with speaking anxiety during classroom presentations at IAIN Bone. Speaking anxiety is a common psychological phenomenon among language learners, particularly when required to speak in front of peers and lecturers. Using a qualitative case study approach, data were collected through semi-structured interviews and classroom observations involving eight students enrolled in an English education program. The findings reveal that students experience anxiety in three major forms: psychological responses such as fear of negative evaluation, overthinking, and self-doubt; physiological reactions including trembling, sweating, dry throat, and increased heart rate; and behavioural manifestations such as avoidance, hesitation, reduced eye contact, and frequent pauses. Students reported that these symptoms significantly limited their ability to express ideas clearly and affected their fluency, confidence, and overall performance during presentations. Although the level and intensity of anxiety varied among participants, all students acknowledged that speaking anxiety had a negative influence on their oral performance. The study highlights the importance of recognizing students’ emotional experiences in EFL classroom practices and calls for the implementation of supportive teaching strategies to reduce anxiety and enhance speaking performance.